Schedule Implementing the Modified Euclidean Distance Method in the Course Planning of the USN Kolaka Information Systems Curriculum - Sutoyo, Muh Nurtanzis; Sumpala Mangkona, Andi Tenri (IT Journal Research and Development, 2022)
Scheduling is needed to anticipate the clash of lecture hours for lecturers in teaching. Some things that need to be considered when arranging a lecture schedule are lecturers, rooms, courses, hours, and days. In this study, the scheduling system uses the Euclidean Distance method by modifying the algorithm. The aim of this study is to prove the Euclidean distance method in the course planning system in universities. In general, to obtain data that will be used in the scheduling system, observations, interviews and bibliographic studies are carried out. From the research results, the lecture scheduling system using the Euclidean Distance method can be used in the scheduling system, especially lecture scheduling. This is proven, that the lecture scheduling system using the Euclidean Distance method does not have a schedule for lecturers who teach more than one course at the same time (collide).